An agent‐based multiattribute reverse auction approach for online secondhand commodities. (18th May 2021) - Liu, Aijun; Xiao, Yaxuan; Li, Zengxian; Wang, Ruiyao
Abstract : Due to the price elasticity of demand for secondhand commodities, it is difficult to establish a quantitative model for the auction. This paper proposes an agent‐based multiattribute reverse auction model to support multicommodity combinatorial auction. First, this paper establishes an agent‐based reverse auction model and introduces the framework, procedures, and protocols of the model in detail. Second, in light of the multicommodity environment, the targets, protocols, auction strategies, and approaches are identified. Finally, by using the proposed agent‐based auction model, both buyers and sellers will reach simultaneous agreements on the details of the commodities to complete the auction.